Qualitative research on "point of sale" technology acceptance in fashion business case study of rumah busana korina - Rifki Ismianto, Muhammad; Raalfaldini Mirzani, Isti (Journal of Business and Management, 2019)
Technology has advanced exponentially in the modern era. The development of technology has certainly increase the ease for human to do so much in so simple methods. This is also the concern for every business existing in the world in order to gain efficiency and effective. Many manufacturers of clothing's have implemented automated machinery and computerization to increase their productivity. Professionals agree that increased technological integration is benefiting companies by capitalizing on industry needs, employee engagement, and is generating increased productivity. One particular business organization in clothing industry is Rumah Busana Korina (RBK) which operates in Hijab clothing. Korina has only just recently improve their internal management towards technological advancements. In November 2018, they implement a system of POS. POS is an automation-based program designed to process all business calculation, particularly that of production and of sales. The author had previously conducted preliminary research on RBK. Without the technology, the owner stated that there may be lots of human error in the business operations of RBK. This intrigued the author to analyze how deep POS technology is implemented compared to its actual capability of the system. One of the method to identify how in-depth a technology is being accepted is by using Technology Acceptance Model. (TAM). TAM is a model that can be used to analyze the factors that influence the acceptance of a system or information system. The objectives of this research are to identify the acceptance of POS implementation towards employees work process in RBK, and to compare the implementation of POS in RBK with the actual intended use of the system. This research uses qualitative approach with utilizing interview and observation as data gathering tools. The author analyses the data using descriptive method. The result of this research shows that POS in Korina has been implemented well in some aspects, but not fully optimized. The usage of POS is limited due to the absence of system training. Key words: Technology Acceptance Model, Point of Sales, Fashion Industry, Rumah Busana Korina.